Termodecomposição da celulose microcristalina e de seus derivados puros e cátions cádmio II adsorvidos - Chahud, Marisa; Ionashiro, Massao; Moreira, José Celso; Campos, Joaquim Theodoro de Souza (Eclética Química, 1996)
.